Case report: successful DaVinci-assisted major liver resection for alveolar echinococcosis - Golriz, Mohammad; Floßmann, Viktoria; Ramouz, Ali; Majlesara, Ali; Kulu, Yakup; Stojković, Marija; Mehrabi, Arianeb (Frontiers in Surgery, 2021)
We report a case of successful robot-assisted major liver resection in a patient with liver alveolar echinococcosis (AE). A 62-year-old male patient was incidentally diagnosed with a large infiltrative lesion in the right liver lobe suspicious for AE. A radical surgical resection as a right-sided hemihepatectomy was indicated. The operation was carried out via a robotic-assisted procedure using the DaVinci Xi Surgical System. The tumor measured 12.4 cm x 8.8 cm and was successfully resected through a suprapubic incision of 13 cm. The patient was free of pain after the second postoperative day. A fluid collection near the resection plate was easily drained without bile leakage. The patient had no surgical complications. Radical resection is inevitable for adequate curative therapy of AE and provides clear margins. Robotic surgery is a relatively new and safe option for curative resection of AE lesions, with remarkable advantages for patients and surgeons.
Gesehen am 04.05.2021